(untitled) (Signifiances (Signifying), 2022)
We discuss here the implications and critical reception of the concept of originary linguistic consciousness formulated and defended by the Dutch philosopher and linguist Hendrik Pos (1898-1955). Emphasizing Pos’s debt to neo-Kantianism and Heinrich Rickert, we show that this notion offers an alternative way of conceptualising the relation of linguistic or semiotic objectivity with individual lived experience. In contrast to Merleau-Ponty’s phenomenological exploration of the speaking subject, to Benveniste’s thematical focus on the problem of the subject as an enunciating instance, or to Saussure’s distinction between language (langue) and speech (parole), Pos elaborates his theory on the basis of a general methodological reflection on the different ways in which language presents itself ("gives itself") empirically.